Engineering of Genetically Arrested Parasites (GAPs) For a Precision Malaria Vaccine - Kreutzfeld, Oriana; Müller, Katja; Matuschewski, Kai (Frontiers in Cellular and Infection Microbiology, 2017)
Continuous stage conversion and swift changes in the antigenic repertoire in response to acquired immunity are hallmarks of complex eukaryotic pathogens, including Plasmodium species, the causative agents of malaria. Efficient elimination of Plasmodium liver stages prior to blood infection is one of the most promising malaria vaccine strategies. Here, we describe different genetically arrested parasites (GAPs) that have been engineered in Plasmodium berghei, P. yoelii and P. falciparum and compare their vaccine potential. A better understanding of the immunological mechanisms of prime and boost by arrested sporozoites and experimental strategies to enhance vaccine efficacy by further engineering existing GAPs into a more immunogenic form hold promise for continuous improvements of GAP-based vaccines. Overall, vaccines that elicit long-lasting protection against malaria in vulnerable populations offer an exciting path of malaria control.